Beneficial impacts of Lactobacillus plantarum and inulin on hypothalamic levels of insulin, leptin, and oxidative markers in diabetic rats. (July 2018) - Valenlia, Khadijeh Bavafa; Morshedi, Mohammad; Saghafi-Asl, Maryam; Shahabi, Parviz; Abbasi, Mehran Mesgari
Graphical abstract: Highlights: L. plantarum and inulin or their combination improved metabolic state in diabetic rats. These supplements increased hypothalamic levels of insulin and leptin in diabetic rats. L. plantarum, inulin, and their combination could ameliorate oxidative status in diabetic rats. Abstract: This study intended to evaluate the effects of Lactobacillus plantarum ( L. plantarum ) and inulin on hypothalamic levels of insulin, leptin, and oxidative markers in diabetic rats. Diabetes was induced by high-fat diet and streptozotocin. The supplements were given to the rats for 8 weeks. Results showed that serum glucose was reduced in the diabetes + L. plantarum (DL), diabetes + inulin (DI), and diabetes + L. plantarum + inulin (DLI) groups. The synbiotic showed increased serum insulin and leptin compared to diabetes sham (DSh) rats, and improved lipid profile compared to DSh and diabetes control (DC) groups. Hypothalamic levels of insulin, leptin, and superoxide dismutase were increased in the DLI group in contrast to DSh group. Malondialdehyde was reduced in the DL, DI, and DLI groups compared to DC group. Therefore, L. plantarum and/or inulin can exert antidiabetic and antioxidant properties via improving insulin resistance, hyperlipidemia as well as hypothalamic levels of insulin, leptin, and oxidative markers in Type 2 diabetes mellitus.